2020
DOI: 10.3389/fonc.2020.00933
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Performance of Minimally Invasive Biopsy in Predicting Breast Pathological Complete Response After Neoadjuvant Systemic Therapy in Breast Cancer: A Meta-Analysis

Abstract: Background: Neoadjuvant systemic therapy (NST) is commonly used in patients with early stage breast cancer before definitive surgery. The standard diagnostic approach for pathologic complete response (pCR) of the breast is breast surgery and pathologic examination. In recent years, several trials investigated the predictive value of image-guided minimally invasive biopsy (MIB) for breast pCR after NST. This study conducted a meta-analysis to evaluate the diagnostic accuracy of MIB. Materials and Methods: We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Authors of that study concluded that breast surgery cannot be omitted in cases showing no residual tumor in tissue biopsies and that standardization of the biopsy procedure is required to improve the predictive values of imaging-guided biopsy [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors of that study concluded that breast surgery cannot be omitted in cases showing no residual tumor in tissue biopsies and that standardization of the biopsy procedure is required to improve the predictive values of imaging-guided biopsy [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent meta-analysis on prediction of pCR by imaging-guided biopsy demonstrated that accuracy of such approaches is rather low irrespectively of the BC subtype. Authors of that study concluded that breast surgery cannot be omitted in cases showing no residual tumor in tissue biopsies and that standardization of the biopsy procedure is required to improve the predictive values of imaging-guided biopsy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some trials have failed to demonstrate how current diagnostic tools (such as histological analysis after needle biopsy) can select patients with a 'real' complete response, and who could therefore theoretically avoid surgery [9]. AI could perform a radiomic analysis and allow a better selection, to identify those patients who can be cured with the exclusive administration of drugs.…”
Section: Diagnosis: From Enhancing Screening To Avoiding Surgery After Neoadjuvant Therapymentioning
confidence: 99%
“…Tumor size or the presence of multifocality or multicentricity were not considered among the selection criteria as they are managed independently in breast cancer [7][8][9][10].…”
Section: Study Population and Management Protocolmentioning
confidence: 99%
“…Targeted axillary dissection (TAD) seems to be the best sampling option, even over marked lymph node biopsy (MLNB) [8]. TAD aims to assess the axillary state after NAST through SNB associated with MLNB, marking the affected lymph node at the time of biopsy using a radio-opaque clip, a ferromagnetic seed, radioiodine or carbon tattooing [8,9].…”
Section: Introductionmentioning
confidence: 99%